The Cuban economy: Data on today's performance and information on tomorrow's projected changes - Al Campbell (The University of Utah, Department of Economics, 2008)
There is widespread discussion both within and outside Cuba concerning what direction the Cuban economy will go under its new interim president Raúl Castro. This short paper is intended to contribute two pieces of information that are needed to intelligently discuss that issue- where Cuba's economy stands today, and what type of reforms Cuba's political and economic leadership say they intend to implement. Its goal is to compactly present current information on some of the key economic issues Cuba faces in regards to both the present and the near future, and thereby give a solidly information-based picture of Cuba's current economic reality. It presents two central conclusions. First, that the evidence supports that there indeed has been real and meaningful accelerated improvement in the Cuban economy in recent years, and at the same time Cuba remains far from being able to meet many of its citizens' economic needs in accord with its own principals of human development. Second, that Cuba intends to continue the process of economic reform that it has been engaged in since at least the early 1990s. This will involve significant restructuring of aspects of how the economy functions, with a central concern with improved efficiency. Cuba intends to introduce some (further) market-mechanisms and in certain areas even markets. But the whole reform process will be conducted in a frame that intends to keep both efficiency considerations and market instruments subordinated to their central goal of building socialism. Two aspects are particularly important in assuring that capitalism-like instruments remain subordinate. The first is an expanded role of the entire population in determining both what is most socially desired, and in presenting ideas on how to improve the economy. The second is the continued use of central planning even as they shift many appropriate decisions in their planning and management process out from the central ministries to the regions and especially to the enterprises.
Keywords: P27; P30; O54; 330; Cuba; Current Economic Conditions; Socialism